Alexandrium minutum cysts in sediment cores from the Eastern Harbour of Alexandria, Egypt - Amany A. Ismael; Ahmed M. Khadr (Oceanologia, 2003)
Alexandrium minutum cysts were studied in sediment cores from its type locality, the Eastern Harbour of Alexandria, following the disappearance of the species from the plankton since 1994. Three cores were sampled in the summer of 1999 along the north-south axis of the harbour. The sediments were subjected to grain size analysis and their organic carbon content was determined. The sediments consisted of medium, coarse and very coarse sand. Grain size and organic carbon content were negatively and significantly correlated in core 1 but followed a parallel trend in cores 2 and 3. Seven dinoflagellate cysts, representing 6 genera were identified from the cores. Their relative abundance showed a remarkable difference. A. minutum cysts contributed a maximum of 17.4% to the total cysts. The distribution profile of A. minutum cysts in the cores reflects the bloom duration but not its productivity. The cyst distribution in the cores is the resultant of two opposite processes, the sedimentation rate and the continuous erosion of the bottom sediments, which is not related to sediment texture.